Study of Stress Tolerance and Resilience of Employees of Penal System - Tsvetkova, N.A.; Kulakova, S.V. (Psihologiâ i pravo, 2019)
The article presents the results of a psychological survey of 90 employees, who determined the level of organizational stress and a degree of development of two professionally important qualities - stress tolerance and resilience. Three psychodiagnostic methods were used: 1) K. McLean scale of organizational stress in N. Vodopyanova's adaptation; 2) the method of studying stress tolerance as a socio-psychological quality of a person; 3) S. Muddy test of resilience. It was found that about 75% of employees deferred by a low overall level of organizational stress and at the same time they had a high level of stress tolerance and resilience; 17% of employees demonstrated a high level of organizational stress, 6% of which was characterized by a low level of stress tolerance. The consistent patterns are established as a result of the correlation analysis: the more active and productive an employee is, the higher his resilience and vice versa; the older the employee, the lower his control indicator; with increasing work experience, flexibility in employee behavior increases. The results of a comparative analysis by gender mark significant differences in the overall level of stress tolerance (higher among women) and the ability of self-knowledge (more developed among men). The psychological conditions for increasing stress tolerance and resilience on an individual level, as well as social and psychological conditions for reducing organizational stress are described. В статье представлены результаты психологического обследования 90 сотрудников, у которых определялись уровень организационного стресса и уровни развития двух профессионально важных качеств — стрессоустойчивости и жизнестойкости. Использовались три методики психодиагностики: 1) шкала организационного стресса К. Маклина в адаптации Н. Водопьяновой; 2) методика исследования стрессоустойчивости как социально-психологического качества личности; 3) тест жизнестойкости С. Мадди. Установлено, что около 75% сотрудников отличались невысоким общим уровнем организационного стресса и при этом имели высокий уровень стрессоустойчивости и жизнестойкости; у 17% сотрудников обнаружен высокий уровень организационного стресса, 6% из которых характенизовались низким уровнем стрессоустойчивости. Приведены результаты корреляционного анализа данных, в ходе которого установлены закономерности: чем более активен и продуктивен сотрудник, тем выше его жизнестойкость, и, наоборот, чем старше сотрудник, тем ниже его показатель контроля; по мере увеличения трудового стажа гибкость в поведении сотрудников повышается. Представлены результаты сравнительного анализа по половому признаку, отмечены достоверные различия по общему уровню стрессоустойчивости (у женщин он выше) и способности самопознания (она более развита у мужчин). Описаны психологические условия повышения стрессоустойчивости и жизнестойкости на индивидуально-личностном уровне, а также социально-психологические условия снижения организационного стресса.